Web-based Parts Inventory Information System at Rizal Auto Workshop Palembang - Nurhachita (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2020)
This study aims to make it easier to find the availability of spare parts, after using the inventory information system can facilitate employees in collecting data on purchase transactions, can help in documenting indent data and consumer data information, data entry goods, transaction data, streamline time and provide solutions and accuracy in the report on incoming and outgoing goods. This system development method uses the Waterfall method, while it uses the system design method of Data Flow Diagrams (DFD), the test system used is a graphical user interface (GUI). The system is made based on web, using the PHP programming language. The results of this study can help leaders and employees to facilitate transaction activities and recap the report at the Rizal Auto Workshop Palembang.